Low-voltage stretchable organic transistors based on elastomer / quantum dot hybrid dielectric materials and methods of making the same

CN116813949BActive Publication Date: 2026-10-09INST OF CHEM CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210263038.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-17
Publication Date
2026-10-09
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

然而,基于这些介电材料所制备的晶体管往往具有高回滞、低开关比、耐拉伸应变能力差(一般为20%~40%)、性能稳定性差等缺点((a)Molina-Lopez,F.;Gao,T.Z.;Kraft,U.;et al.Nat.Commun.2019,10,2676.(b)Wang,X.;Yu,C.J.J.Mater.Res.2019,1.),无法满足电子器件长期使用和低功耗的要求

Benefits of technology

[0048] Beneficial Effects: This invention, by optimizing the blending conditions of elastomeric polymers and quantum dot solutions and controlling the microphase separation and aggregation behavior of quantum dots in the elastomeric polymer, prepared an ultra-flexible (tensile strain > 600%), high-dielectric large-area hybrid polymer film. Furthermore, it yielded a low-voltage, high-performance intrinsically stretchable organic transistor. The fabrication process is simple, low-cost, and enables large-area integration. The intrinsically stretchable organic transistor prepared by this invention exhibits low operating voltage, high field-effect characteristics, and excellent tensile strain resistance; it also demonstrates good performance stability and uniformity, broadening the application prospects of stretchable organic transistors in low-voltage, high-performance electronic skin and wearable X-ray detection fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003551417190000011
    Figure HDA0003551417190000011
  • Figure HDA0003551417190000012
    Figure HDA0003551417190000012
  • Figure HDA0003551417190000013
    Figure HDA0003551417190000013
Patent Text Reader

Abstract

The application discloses a low-voltage stretchable organic transistor based on elastomer / quantum dot hybrid dielectric material. From bottom to top, the transistor comprises a stretchable substrate, a stretchable gate electrode, a stretchable hybrid polymer dielectric layer, a stretchable polymer semiconductor layer, and a stretchable source electrode and a stretchable drain electrode located in the same plane, wherein the transistor is a bottom gate top contact structure. The application optimizes the blending conditions of elastomer polymer and quantum dots and regulates the micro-phase separation and aggregation behavior of quantum dots in the elastomer, thereby preparing a super-flexible (stretching strain > 600%) and high-dielectric-constant large-area hybrid polymer film. Based on the polymer dielectric film, the prepared stretchable organic transistor not only has low operating voltage (lower than 5 volts), high carrier mobility, high on-off current ratio, low threshold voltage and low sub-threshold slope, but also has good performance stability, light transmittance, skin conformability and excellent tensile strain resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wearable and skin-like electronic device technology, specifically relating to a method for preparing ultra-flexible, high-dielectric large-area polymer thin films, and a low-voltage stretchable organic transistor based on an elastomer / quantum dot hybrid dielectric material. Background Technology

[0002] Wearable and skin-like electronic devices can mimic the human skin's perception of external stimuli such as pressure, temperature, humidity, and chemicals, and are therefore widely used in emerging fields such as physiological monitoring, medical diagnosis, medical implantation, and artificial intelligence ((a) Wang, S.; Xu, J.; Wang, W.; et al. Nature 2018, 555, 83. (b) Oh, JY; Rondeau-Gagné S.; Chiu, Y.-C.; et al. Nature 2016, 539, 411. (c) Tee, BCK; Chortos, A.; Berndt, A.; et al. Science 2015, 350, 313.). Organic thin-film transistors (OTCs) possess excellent intrinsic flexibility, lightweight, high sensitivity, ease of integration, and large-area fabrication capabilities. They can also serve as fundamental components for scrolling displays, flexible smart cards, conformal sensors, and electronic skin (Liu, K.; Ouyang, B.; Guo, XJ; et al. npj Flex. Electron. 2022, 1.). In recent years, thanks to the collaborative efforts of researchers, intrinsically stretchable organic transistors have developed rapidly, with mobilities far exceeding those of amorphous silicon transistors (0.1 cm⁻¹). 2 V -1 s -1Furthermore, it exhibits stable electrical properties even under tensile strains up to 100% ((a)Xu,J.;Wang,S.;Wang,G.-JN;et al.Science 2017,355,aah4496.(b)Xu,J.;Wu,H.-C.;Zhu,C.;et al.Nat.Mater.2019,18,594.). To ensure the safety and ease of use of electronic skin devices, it is essential to reduce the operating voltage of stretchable transistors. However, currently reported stretchable organic transistors often have relatively high operating voltages (typically 30–80V), which are difficult to meet the requirements for electronic skin applications. Its high operating voltage is mainly due to two factors: first, because stretchable dielectric materials are often selected from elastomeric polymers, such as PDMS and SEBS, and these materials have relatively low dielectric constants, only 2 to 2.5; second, because stretchable electrode materials are often selected from carbon nanotubes or silver nanowires, and these two types of electrode films have very high roughness, so it is necessary to increase the dielectric layer thickness (generally 1500 to 200 nm).

[0003] Currently, low-voltage transistors mainly employ high-dielectric materials such as polymer electrolytes or ion gels as their dielectric layers, although these materials can significantly reduce the operating voltage of transistors. However, transistors fabricated based on these dielectric materials often suffer from drawbacks such as high hysteresis, low on / off ratio, poor tensile strain resistance (typically 20%–40%), and poor performance stability ((a) Molina-Lopez, F.; Gao, TZ; Kraft, U.; et al. Nat. Commun. 2019, 10, 2676. (b) Wang, X.; Yu, CJJ Mater. Res. 2019, 1.), failing to meet the requirements for long-term use and low power consumption in electronic devices. Therefore, finding a simple and effective method to fabricate ultra-flexible, high-dielectric large-area polymer films, and further realizing low-voltage, high-performance stretchable organic transistors, is of great research significance and commercial value for expanding the fields of low-power electronic skin and wearable X-ray detection. Summary of the Invention

[0004] In view of the shortcomings of the existing research, the purpose of this invention is to prepare an ultra-flexible (tensile strain > 600%), high dielectric large-area hybrid polymer film by optimizing the blending conditions of elastopolymer and quantum dot solution and controlling the microphase separation and aggregation behavior of quantum dots in elastopolymer.

[0005] Another object of the present invention is to provide a low-voltage, high-performance stretchable organic transistor based on an elastomer / quantum dot hybrid dielectric material. This transistor exhibits a low operating voltage (<6V) and high mobility (0.1cm). 2 V-1 s -1 ), high switching current ratio (10) 5 It features low threshold voltage (<1V), low subthreshold slope (0.5V / de), high tensile strain (>100%), and good performance stability (>30 days).

[0006] The low-voltage stretchable organic transistor provided by the present invention comprises, from bottom to top, a stretchable substrate, a stretchable gate electrode, a stretchable hybrid polymer dielectric layer, a stretchable polymer semiconductor layer, and a stretchable source electrode and a stretchable drain electrode on the same plane.

[0007] The low-voltage stretchable organic transistor described in this invention has a bottom-gate top-contact structure.

[0008] The stretchable hybrid polymer dielectric layer in the low-voltage stretchable organic transistor is prepared by controlling the microphase separation and aggregation behavior of the elastomer polymer and quantum dots.

[0009] The elastomer polymer is selected from any one of polydimethylsiloxane (PDMS), hydrogenated styrene-butadiene block copolymer (SEBS), polyurethane elastomer (PU), styrene-butadiene rubber (SBS), and natural rubber (NR);

[0010] The quantum dots are characterized by being uncharged, having high dielectric properties, and narrow particle size, such as carbon quantum dots (with a size of 1-5 nm).

[0011] The mass ratio of the elastomer polymer to the quantum dots is 100:0.5 to 100:10, preferably 100:1.5 to 100:5, specifically 100:3.5 or 100:5.

[0012] The microphase separation and aggregation behavior is achieved by modulating the substrate surface energy;

[0013] The surface energy of the substrate is achieved through ultraviolet ozonolysis treatment, and its surface energy can be regulated within the range of 10-30 millijoules per square centimeter.

[0014] The thickness of the stretchable hybrid polymer dielectric layer can be 1300-2500 nm, preferably 1500-1800 nm.

[0015] In the aforementioned low-voltage stretchable organic transistor, the stretchable polymer semiconductor layer is prepared from a stretchable hybrid polymer blend system;

[0016] The stretchable hybrid polymer blend system is a mixture of elastomeric polymers and conjugated polymers;

[0017] The elastomeric polymer is the same as the elastomeric polymer used in the stretchable hybrid polymer dielectric layer;

[0018] The conjugated polymer is any one of poly(2,5-bis(2-octyldodecyl)-3,6-bis(thiophen-2-yl)dionepyrrole[3,4-c]pyrrole-1,4-dione-alt-thiophen[3,2-b]thiophene) (DPPT-TT), poly(2,5-bis(3-alkylthiophen-2-yl)thiophene[3,2-b]thiophene) (PBTTT), poly(tetrathiopheneacetic acid dionepyrrole) (PTDPPTFT4), polyisoindigodithiophene (PII2T), and poly(3-hexylthiophene) (P3HT);

[0019] The mass ratio of the conjugated polymer to the elastomer polymer is 1:9 to 9:1, preferably 3:7 to 5:5.

[0020] The thickness of the stretchable polymer semiconductor layer is 30-100 nm, preferably 50-70 nm.

[0021] In the aforementioned low-voltage stretchable organic transistor, the stretchable substrate is prepared from any one of the elastomeric polymers in the stretchable hybrid polymer dielectric layer;

[0022] The thickness of the stretchable substrate is 100μm to 2mm, preferably 600-1000μm.

[0023] In the aforementioned low-voltage stretchable organic transistor, the stretchable gate electrode, the stretchable source electrode, and the stretchable drain electrode are all made of carbon nanotube material;

[0024] Furthermore, the carbon nanotube material is a single-walled carbon nanotube, including any one of the types P2-SWNT, P3-SWNT, P5-SWNT, P8-SWNT, and P9-SWNT;

[0025] The solvents used are ethanol, isopropanol, water, or a mixture thereof.

[0026] The method for fabricating the above-mentioned low-voltage stretchable organic transistor provided by the present invention includes the following steps:

[0027] (1) The stretchable substrate, the stretchable gate electrode, the stretchable hybrid polymer dielectric layer, the stretchable polymer semiconductor layer, the stretchable source electrode, and the stretchable drain electrode are respectively fabricated on a substrate with a self-assembled molecular layer;

[0028] (2) Use pointed tweezers to transfer the stretchable substrate from the substrate with the self-assembled molecular layer, and then gently cover the stretchable substrate on the stretchable gate electrode from one side; transfer the stretchable gate electrode to the stretchable substrate by a thermal bonding-transfer method; then use the same method and steps to sequentially transfer the stretchable hybrid polymer dielectric layer, the stretchable polymer semiconductor layer, and the stretchable source electrode and the stretchable drain electrode located on the same plane to the stretchable gate electrode, thereby obtaining a low-voltage stretchable organic transistor based on an elastomer / quantum dot hybrid dielectric material.

[0029] In the above preparation steps, the substrate is selected from any one of silicon wafers, glass, ceramics, and quartz;

[0030] The substrate is ultrasonically cleaned sequentially with detergent, deionized water, acetone and ethanol, dried with a nitrogen gun, and then subjected to ultraviolet ozonolysis to obtain a clean substrate.

[0031] The ultrasonic conditions are: ultrasonic power of 10-100 watts, ultrasonic time of 1-30 minutes, and ultrasonic frequency of 10-100 kilohertz.

[0032] The conditions for the ultraviolet ozonolysis treatment are: treatment time of 10-30 minutes;

[0033] The substrate with the self-assembled molecular layer is prepared by heating or immersing the clean substrate in a solution under vacuum conditions with any one of octadecyltrimethoxysilane, octadecyltrichlorosilane, octadecyltrichlorosilane, and phenyltrichlorosilane.

[0034] The conditions for the vacuum heating treatment are: vacuum degree of 0.1 Pascal, heating temperature of 50-150℃, and heating time of 1-5 hours.

[0035] The conditions for the solution immersion treatment are as follows: the solvent used is any one of n-hexane, n-heptane, isohexane, and cyclohexane; the volume ratio of the octadecyltrimethoxysilane, octadecyltrichlorosilane, octadecyltrichlorosilane, or phenyltrichlorosilane to the n-hexane, n-heptane, isohexane, or cyclohexane is 1:200-1:1000, and the immersion time is 0.1-3 hours.

[0036] In the above preparation steps, the stretchable substrate, the stretchable hybrid polymer dielectric layer, and the stretchable polymer semiconductor layer are all prepared by solution deposition.

[0037] The solution deposition method is any one of drop coating, spin coating, blade coating, roller coating, brush coating, and stretch coating;

[0038] The solvent used in the solution deposition method is toluene, xylene, methane, chloroform, dichloromethane, n-hexane, or cyclohexane;

[0039] The solution concentration of the stretchable substrate is 100-300 mg / mL;

[0040] The solution concentration of the stretchable hybrid polymer dielectric layer is 50-100 mg / mL;

[0041] The solution concentration of the stretchable polymer semiconductor layer is 5-15 mg / mL.

[0042] In the above preparation steps, the stretchable gate electrode, the stretchable source electrode, and the stretchable drain electrode are all prepared by spray coating.

[0043] The solvent used is water, ethanol, isopropanol, or a mixture thereof;

[0044] The spraying conditions are as follows: the temperature of the substrate is 60-120℃, the distance between the spray gun nozzle and the substrate is 5-12mm, the spraying rate is 0.3-3mL / min, and the spraying amount is 1-3mL.

[0045] To ensure high resolution of the stretchable gate electrode, the stretchable source electrode, and the stretchable drain electrode, a substrate with a self-assembled molecular layer is placed between a strong magnet and a patterned nickel or iron mask.

[0046] In the above preparation steps, the heat bonding process is carried out in a vacuum drying oven;

[0047] The conditions for heat bonding are: vacuum degree of 0.1 to 3 Pascals, temperature of 30 to 80°C, and heat treatment time of 0.1 to 1 hour.

[0048] Beneficial Effects: This invention, by optimizing the blending conditions of elastomeric polymers and quantum dot solutions and controlling the microphase separation and aggregation behavior of quantum dots in the elastomeric polymer, prepared an ultra-flexible (tensile strain > 600%), high-dielectric large-area hybrid polymer film. Furthermore, it yielded a low-voltage, high-performance intrinsically stretchable organic transistor. The fabrication process is simple, low-cost, and enables large-area integration. The intrinsically stretchable organic transistor prepared by this invention exhibits low operating voltage, high field-effect characteristics, and excellent tensile strain resistance; it also demonstrates good performance stability and uniformity, broadening the application prospects of stretchable organic transistors in low-voltage, high-performance electronic skin and wearable X-ray detection fields. Attached Figure Description

[0049] Figure 1 This is a schematic diagram of the structure of the low-voltage stretchable organic transistor based on an elastomer / quantum dot hybrid polymer dielectric material disclosed in this invention.

[0050] Figure 2 This is a large-area (35cm×25cm) elastomer / carbon quantum dot hybrid polymer dielectric film prepared in Example 1 of the present invention.

[0051] Figure 3 These are the characteristic transfer curves of the stretchable organic transistors prepared in Examples 1, 2, and Comparative Example 1 of this invention. Figure 3 (a) shows the relationship between the source-drain current and the gate voltage; Figure 3 (b) represents the source-drain current. 1 / 2 Relationship with gate voltage.

[0052] Figure 4 (a) is the output transfer curve of the stretchable organic transistor prepared in Example 1 of the present invention; Figure 4 (b) is the output transfer curve of the stretchable organic transistor prepared in Example 2 of the present invention.

[0053] Figure 5 (a) shows the relationship between the on-state current and the switching current ratio of the stretchable organic transistor prepared in Example 1 of the present invention and the tensile strain. Figure 5 (b) shows the relationship between the threshold voltage and subthreshold slope of the stretchable organic transistor prepared in Example 1 of the present invention and tensile strain. Detailed Implementation

[0054] The low-voltage stretchable organic transistor based on an elastomer / quantum dot hybrid dielectric material provided by this invention has an upper electrode structure. Its structure is as follows: Figure 1 As shown, from bottom to top, it includes a stretchable substrate, a stretchable gate electrode, a stretchable hybrid polymer dielectric layer, a stretchable polymer semiconductor layer, and a stretchable source electrode and a stretchable drain electrode located on a plane; wherein the stretchable hybrid polymer dielectric layer is prepared by optimizing the blending conditions of the elastomer polymer and the quantum dot solution and controlling the microphase separation and aggregation behavior of the quantum dots in the elastomer polymer.

[0055] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments.

[0056] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; unless otherwise specified, the reagents and materials described are commercially available.

[0057] In this invention, the mechanical and electrical properties of the low-voltage stretchable organic transistor were measured under atmospheric and room temperature conditions.

[0058] Example 1:

[0059] This embodiment fabricates a low-voltage stretchable organic transistor based on an elastomer / quantum dot hybrid dielectric material according to the following steps:

[0060] 1) Using a silicon wafer as a substrate, ultrasonically clean the silicon wafer for 5 minutes at 20W power and 30 kHz frequency with detergent, deionized water, acetone and ethanol in sequence. After drying with a nitrogen gun, treat the cleaned silicon wafer with ultraviolet ozone (power 60Hz) for 20 minutes. Then, place the cleaned silicon wafer and 1 μL of octadecyltrimethoxysilane in the same petri dish and place the petri dish in a vacuum drying oven at 0.1 Pa vacuum degree and 120℃ for 3 hours. After the vacuum drying oven cools to room temperature, remove the petri dish to obtain a silicon wafer with a self-assembled molecular layer.

[0061] 2) Place the silicon wafer with the self-assembled molecular layer on a hot plate. Slowly draw 0.5 ml of SEBS toluene solution (concentration 150 mg / mL) with a 1 mL syringe and uniformly drop it onto the silicon wafer with the self-assembled molecular layer. Then, maintain the temperature at 40°C for 2 hours and then at 90°C for 1 hour to obtain a stretchable substrate with a thickness of 1 mm. (Note: To ensure that no air bubbles appear in the prepared stretchable substrate and that there is good surface uniformity, the drop-coating rate should be as slow as possible. The last two drops of SEBS toluene solution should not be dropped onto the silicon wafer with the self-assembled molecular layer.)

[0062] 3) Place the silicon wafer with the self-assembled molecular layer prepared in step 1) on a magnet, and then place the patterned nickel mask on the silicon wafer to tightly attach the mask to the silicon wafer with the self-assembled molecular layer. Gently place the magnet, silicon wafer and mask on a hot stage at 60°C for 5 minutes. Use a 2mL pipette to transfer 1.5mL of carbon nanotube P3-SWNT isopropanol solution (0.2mg / mL) into the volume chamber of the spray gun, and then uniformly spray it onto the silicon wafer with the self-assembled molecular layer at a rate of 0.15mL / min (wherein, the distance between the spray gun nozzle and the silicon wafer is 8mm) to obtain the patterned stretchable gate electrode.

[0063] 4) Place the silicon wafer with the self-assembled molecular layer prepared in step 1) at the center of the spin coater rotor. Use a 1 mL pipette to draw 200 μL of a mixed solution of SEBS and carbon quantum dots (solvent is toluene, mass ratio of SEBS to carbon quantum dots is 100:3.5, concentration of mixed solution is 100 mg / mL). Then, uniformly drop 160 μL of the SEBS:carbon quantum dot mixed solution onto the silicon wafer with the self-assembled molecular layer. Start the spin coater and maintain a speed of 1000 rad / min for 1 min. Finally, remove the silicon wafer and anneal it on a hot plate at 80°C for 30 min to obtain a stretchable hybrid polymer dielectric layer with a thickness of 1800 nm. Its physical image is shown in Figure 2.

[0064] 5) Place the silicon wafer with the self-assembled molecular layer prepared in step 1) at the center of the spin coater rotor. Use a 100 μL pipette to draw 50 μL of a chlorobenzene solution of poly(2,5-bis(2-octyldodecyl)-3,6-di(thiophene-2-yl)dionepyrrolo[3,4-c]pyrrolo-1,4-dione-3-thiophenolo[3,2-b]thiophene) / hydrogenated styrene-butadiene block copolymer (wherein the mass ratio of the two polymers is 3:7 and the concentration of the mixture solution is 10 mg / mL). Then, uniformly drop 35 μL of the solution onto the silicon wafer. Start the spin coater and maintain a speed of 2000 rad / min for 1 min. Finally, remove the silicon wafer and place it on a hot plate at 150°C for 20 minutes to obtain a stretchable polymer semiconductor layer with a thickness of 70 nm.

[0065] 6) Place the silicon wafer with the self-assembled molecular layer prepared in step 1) on a magnet, and then place the patterned nickel mask on the silicon wafer to tightly attach the mask to the silicon wafer with the self-assembled molecular layer. Gently place the magnet, silicon wafer and mask on a hot stage at 110°C for 15 minutes. Then, use a 2mL pipette to draw 1.5mL of isopropanol solution of carbon nanotube P3-SWNT (concentration of 0.15mg / mL) and spray it uniformly onto the silicon wafer with the self-assembled molecular layer at a rate of 0.1mL / min (wherein the distance between the nozzle of the spray gun and the silicon wafer is 9mm). This will give you the patterned stretchable source electrode and stretchable drain electrode (channel length and channel width are 200μm and 4000μm, respectively).

[0066] 7) Gently peel the stretchable substrate off the substrate with the self-assembled molecular layer using pointed tweezers. Then, gently cover the stretchable gate electrode with the stretchable substrate from one side and place it in a vacuum drying oven with a vacuum degree of 0.1 Pa at 60°C for 20 minutes. After the temperature drops to room temperature, gently transfer the stretchable substrate off using pointed tweezers. Through this process, the stretchable gate electrode can be transferred onto the stretchable substrate. Then, using the same method and steps, sequentially transfer the stretchable hybrid polymer dielectric layer, the stretchable polymer semiconductor layer, and the stretchable source electrode and the stretchable drain electrode located on the same plane onto the stretchable gate electrode to obtain a low-voltage stretchable organic transistor based on an elastomer / carbon quantum dot hybrid dielectric material, with the structure as shown below. Figure 1 As shown.

[0067] Example 2

[0068] The preparation method was exactly the same as in Example 1, except that the mixed solution of SEBS and carbon quantum dots in step 4) (solvent was toluene, the mass ratio of SEBS and carbon quantum dots was 100:3.5, and the concentration of the mixed solution was 100 mg / mL) was changed to a mixed solution of SEBS and carbon quantum dots (solvent was toluene, the mass ratio of SEBS and carbon quantum dots was 100:5, and the concentration of the mixed solution was 105 mg / mL).

[0069] Comparative Example 1:

[0070] The preparation method was exactly the same as in Example 1, except that the mixed solution of SEBS and carbon quantum dots in step 4) (solvent was toluene, the mass ratio of SEBS to carbon quantum dots was 100:3.5, and the concentration of the mixed solution was 100 mg / mL) was replaced with a toluene solution of SEBS (concentration was 85 mg / mL). The thickness of the stretchable polymer dielectric layer prepared in Comparative Example 1 was consistent with the thickness of the stretchable hybrid polymer dielectric layer prepared in Example 1, which was approximately 1900 nm.

[0071] Figure 2 This is the large-area (30cm × 20cm) elastomer / carbon quantum dot hybrid polymer dielectric film prepared in Example 1. Figure 2 It can be seen that this large-area hybrid polymer dielectric film exhibits high optical transparency and good surface uniformity. Figure 3 (a) and (b) are the characteristic transfer curves of the stretchable organic transistors prepared in Examples 1, 2, and Comparative Example 1 of this invention. Compared to Comparative Example 1, the stretchable organic transistors prepared in Examples 1 and 2 exhibit better on-state current and lower threshold voltage at an operating voltage of 6V. Furthermore, combined with the characteristics of… Figure 4 It can be seen that the stretchable organic transistors prepared in Examples 1 and 2 exhibit ideal and saturated output curves at operating voltages of 4–6V, indicating that the stretchable organic transistors prepared based on SEBS / carbon quantum dot hybrid dielectric films can achieve low-voltage operation and possess high electrical performance. Meanwhile, from Figure 5 It is evident that the stretchable organic transistor prepared in Example 1 maintains relatively stable field-effect performance (including on-state current, on-off current ratio, threshold voltage, and subthreshold slope) even under biaxial tensile strain ranging from 0% to 100%, and its field-effect performance recovers to its initial values ​​after the tensile strain is released. These experimental results demonstrate that the stretchable organic transistor prepared based on stretchable hybrid polymer dielectric films not only achieves low-voltage operation but also possesses high field-effect performance, high resistance to mechanical deformation, and ideal large-area solution processability, providing a simple and effective strategy for future low-power electronic skin and wearable X-ray detection.

Claims

1. A method for preparing a hybrid polymer film with ultra-flexibility and high dielectric properties, comprising the following steps: The process involves blending elastomeric polymers with quantum dots and controlling the microphase separation and aggregation behavior of the elastomeric polymers and quantum dots. The elastomer polymer is any one of polydimethylsiloxane, hydrogenated styrene-butadiene block copolymer, polyurethane elastomer, styrene-butadiene rubber and natural rubber; The quantum dots are characterized by being uncharged, having high dielectric properties, and having narrow particle size; the quantum dots are carbon quantum dots. The mass ratio of the elastomer polymer to quantum dots is 100:0.5 to 100:10; The microphase separation and aggregation behavior is achieved by regulating the substrate surface energy; the regulation of the substrate surface energy is achieved by ultraviolet ozonolysis treatment, and the surface energy regulation range is 10-30 millijoules per square centimeter.

2. The hybrid polymer film prepared by the method of claim 1.

3. A low-voltage stretchable organic transistor, the structure of which comprises, from bottom to top: A stretchable substrate, a stretchable gate electrode, a stretchable hybrid polymer dielectric layer, a stretchable polymer semiconductor layer, and a stretchable source electrode and a stretchable drain electrode in the same plane; The low-voltage stretchable organic transistor has a bottom-gate top-contact structure. The stretchable hybrid polymer dielectric layer is composed of the hybrid polymer film as described in claim 2.

4. The low-voltage stretchable organic transistor according to claim 3, characterized in that: The stretchable hybrid polymer dielectric layer is prepared by blending an elastomer polymer with quantum dots and controlling the microphase separation and aggregation behavior of the elastomer polymer and quantum dots. The elastomer polymer is any one of polydimethylsiloxane, hydrogenated styrene-butadiene block copolymer, polyurethane elastomer, styrene-butadiene rubber and natural rubber; The thickness of the stretchable hybrid polymer dielectric layer is 1300-2500 nm.

5. The low-voltage stretchable organic transistor according to claim 3, characterized in that: The stretchable polymer semiconductor layer is prepared from a stretchable hybrid polymer blend system; The stretchable hybrid polymer blend system is a blend of an elastomeric polymer and a conjugated polymer; The conjugated polymer is any one of poly(2,5-bis(2-octyldodecyl)-3,6-bis(thiophen-2-yl)dionepyrrole[3,4-c]pyrrole-1,4-dione-alt-thiophene[3,2-b]thiophene), poly(2,5-bis(3-alkylthiophen-2-yl)thiophene[3,2-b]thiophene), poly(tetrathiopheneacetic acid dionepyrrole), polyisoindigodithiophene, and poly(3-hexylthiophene); The elastomer polymer is any one of polydimethylsiloxane, hydrogenated styrene-butadiene block copolymer, polyurethane elastomer, styrene-butadiene rubber and natural rubber; The mass ratio of the conjugated polymer to the elastomer polymer is 1:9 to 9:1; The thickness of the stretchable polymer semiconductor layer is 30-100 nm.

6. The low-voltage stretchable organic transistor according to claim 3, characterized in that: The stretchable gate electrode, the stretchable source electrode, and the stretchable drain electrode are all made of carbon nanotube material; The carbon nanotube material is a single-walled carbon nanotube, including any one of the following types: P2-SWNT, P3-SWNT, P5-SWNT, P8-SWNT, and P9-SWNT. The stretchable substrate is made of an elastomeric polymer; the elastomeric polymer is any one of polydimethylsiloxane, hydrogenated styrene-butadiene block copolymer, polyurethane elastomer, styrene-butadiene rubber, and natural rubber; The thickness of the stretchable substrate is 100 µm-2 mm.

7. A method for fabricating a low-voltage stretchable organic transistor according to any one of claims 3-6, comprising the following steps: 1) The stretchable substrate, the stretchable gate electrode, the stretchable hybrid polymer dielectric layer, the stretchable polymer semiconductor layer, the stretchable source electrode, and the stretchable drain electrode are respectively fabricated on a substrate with a self-assembled molecular layer; 2) Use pointed tweezers to transfer the stretchable substrate off the substrate with the self-assembled molecular layer, and then gently cover the stretchable substrate on the stretchable gate electrode from one side; The stretchable gate electrode is transferred to the stretchable substrate using a thermal bonding-transfer method; then, the same method and steps are used to sequentially transfer the stretchable hybrid polymer dielectric layer, the stretchable polymer semiconductor layer, and the stretchable source electrode and the stretchable drain electrode located on the same plane to the stretchable gate electrode, thereby obtaining the low-voltage stretchable organic transistor.

8. The preparation method according to claim 7, characterized in that: The substrate is selected from any one of silicon wafers, glass, ceramics and quartz; The substrate is ultrasonically cleaned sequentially with detergent, deionized water, acetone and ethanol, dried with a nitrogen gun, and then subjected to ultraviolet ozonolysis to obtain a clean substrate. The substrate with the self-assembled molecular layer is prepared by heating or immersing the clean substrate in a solution under vacuum conditions with any one of octadecyltrimethoxysilane, octadecyltrichlorosilane, octadecyltrichlorosilane, and phenyltrichlorosilane.

9. The preparation method according to claim 7 or 8, characterized in that: The stretchable substrate, the stretchable hybrid polymer dielectric layer, and the stretchable polymer semiconductor layer are prepared by solution deposition. The solution deposition method is any one of drop coating, spin coating, blade coating, roller coating, brush coating, and stretch coating; The solvent used in the solution deposition method is toluene, xylene, methane, chloroform, dichloromethane, n-hexane, or cyclohexane; The solution concentration of the stretchable substrate is 100-300 mg / mL; The solution concentration of the stretchable hybrid polymer dielectric layer is 50-100 mg / mL; The solution concentration of the stretchable polymer semiconductor layer is 5-15 mg / mL; The stretchable gate electrode, the stretchable source electrode, and the stretchable drain electrode are all fabricated by spraying. The spraying conditions are as follows: the substrate temperature is 60-120 °C, the distance between the spray gun nozzle and the substrate is 5-12 mm, the spraying rate is 0.3-3 mL / min, and the spraying amount is 1-3 mL. The heat bonding process is carried out in a vacuum drying oven; The conditions for heat bonding are: vacuum degree of 0.1~3 Pascals, temperature of 30~80 °C, and heat treatment time of 0.1~1 hour.

Citation Information

Patent Citations

  • Organic field-effect multilevel transistor memory on basis of light regulation and control and method for preparing organic field-effect multilevel transistor memory

    CN109326713A

  • Intrinsic stretchable organic parallel heterojunction opto-transistor and preparation method thereof

    CN113707808A